Private Wells 101: Bacterial Contamination and Shock Chlorination - Yilin Zhuang; Mary Lusk (EDIS)
Private well users are responsible for the management and protection of their wells. This new 4-page EDIS publication is for Florida homeowners who are interested in learning more about their well-water system and understanding how to properly shock, or disinfect, the well if there is evidence of drinking water contamination. Written by Yilin Zhuang and Mary Lusk, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss700